PREFERENCE AND LITERACY: FISHERMEN AND MARINE FARMERS IN SMALL ISLANDS REGION TO USE FINTECH - Ngangun, Tati Atia; Pentury, Frischilla; Teniwut, Roberto Mario Kabi; Hamid, Syahibul Kahfi; Rahantoknam, Meyske Angel; Hasyim, Cawalinya Livsanthi; Teniwut, Wellem Anselmus (Jurnal Riset Bisnis dan Manajemen, 2024)
The aimed of the study was to explore knowledge as proxy to literacy to the preference to use fintech by fishermen and marine farmers in Kei Islands, Maluku Indonesia. Data collected used purposive sampling with total 318 samples used by questionnaires, we then use smartPLS to analysis data using path analysis. The result showed that knowledge has positive direct and significant effect on the preference to use fintech, moreover, the more familiar fishermen and marine farmer to ICT, higher preference to use fintech, also more options available to fintech can increase the intention to get finance by MSMEs. This important to have empirical information on MSMEs in small islands region on their view to use fintech as a baseline to plan further effective plans to help MSMEs to develop their business.